Dynamic contrast-enhanced sonography and dynamic contrast-enhanced magnetic resonance imaging for preoperative diagnosis of infected nonunions - Fischer, Christian; Preuß, Eva-Maria; Tanner, Michael Christopher; Bruckner, Thomas; Krix, Martin; Amarteifio, Erick; Miska, Matthias; Moghaddam-Alvandi, Arash; Schmidmaier, Gerhard; Weber, Marc-André (Journal of ultrasound in medicine, 2016)
Objectives Bone regeneration depends on perfusion of the fracture tissue, whereby hypervascularity is associated with infection, which itself causes nonunions. To date, nonunion perfusion has not been assessed with contrast-enhanced sonography. The aim of this study was to evaluate the potential of contrast-enhanced sonography in the analysis of nonunion tissue perfusion. Methods Nonunion vascularity of 31 patients before revision surgery was prospectively examined with qualitative contrast-enhanced sonography and dynamic contrast-enhanced magnetic resonance imaging (MRI). Time-intensity curves from 2-minute contrast-enhanced sonographic video clips were generated, and parameters such as wash-in rate, rise time, and peak enhancement were quantified. On dynamic contrast-enhanced MRI, the initial area under the enhancement curve was quantified. Preoperative radiographs, computed tomograms, the clinical nonunion score, laboratory infection features, as well as contrast-enhanced sonographic and dynamic contrast-enhanced MRI perfusion were correlated with microbiological results from the nonunion tissue. Results Both qualitative and quantitative contrast-enhanced sonography showed significant differences between infected and aseptic nonunions (P = .015 and .020). The qualitative dynamic contrast-enhanced MRI analysis was not significant (P= .244), but after quantification, a strong correlation (P = .007) with microbiological results was noted. A receiver operating characteristic analysis calculated ideal cutoff values for quantitative contrast-enhanced sonography and dynamic contrast-enhanced MRI so that their combination detected infected nonunions with sensitivity and specificity of 88.9% and 77.3%, respectively. Clinical, radiologic, and laboratory examinations did not correlate with microbiological results (P > .05). Conclusions Contrast-enhanced sonography can visualize the vascularity of nonunions in real time, while quantification software allows for a semiobjective evaluation of bone perfusion. The correlations of both quantitative contrast-enhanced sonography and dynamic contrast-enhanced MRI with microbiological results show their high value for differentiation of infected from aseptic nonunions.